2020–2021 Vegetable Production Handbook: Chapter 10. Minor Vegetable Crop Production - Christian F. Miller; Qingren Wang; Ramdas Kanissery; Eugene J. McAvoy; Richard N. Raid; Crystal A. Snodgrass; Julien Beuzelin; Dakshina R. Seal; Alicia J. Whidden; Johan Desaeger; Shouan Zhang; Peter J. Dittmar (EDIS)
This chapter covers production of celery, okra, and parsley.